1997
DOI: 10.1021/jf9603238
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Isomers of Inositol Mono- to Hexaphosphates in Selected Foods and Intestinal Contents Using High-Performance Ion Chromatography

Abstract: A sensitive high-performance ion chromatography (HPIC) method for separation and quantitative determination of inositol mono- to hexaphosphate (IP1−IP6) isomers in selected foods and intestinal contents is described. The method includes extraction of samples with HCl, separation of the inositol phosphates from the crude extract by anion-exchange chromatography, separation on high-performance ion-exchange columns with gradient elution in two combined HPIC systems, and detection using either postcolumn reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 21 publications
3
110
1
1
Order By: Relevance
“…However, Skoglund et al (1997a) showed that the concentration of InsP 1 -P was lower than the concentration of the other lower inositol phosphates in ileal digesta. Therefore, the accumulation of InsP 1 -P was expected to be negligible in this study.…”
Section: Discussionmentioning
confidence: 92%
“…However, Skoglund et al (1997a) showed that the concentration of InsP 1 -P was lower than the concentration of the other lower inositol phosphates in ileal digesta. Therefore, the accumulation of InsP 1 -P was expected to be negligible in this study.…”
Section: Discussionmentioning
confidence: 92%
“…The isomers of inositol penta-and tetraphosphates in fecal samples were determined employing the method of Skoglund et al (1997). The latter method includes extraction of samples with HCl, separation of the inositol phosphates from the crude extract by anionexchange chromatography, separation on high-performance ion-exchange columns with gradient elution and detection using post-column reaction and UV detection.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis and identification of the IP 6 degradation products IP 5 -IP 2 , was performed using the same system as for the rapid IP 6 analysis, but with a gradient elution system as described by Skoglund and co-workers [22]. Peak identification was done by analyzing a chemically hydrolyzed sodium phytate sample.…”
Section: Identification Of Phytate Degradation Products Ip 5 -Ipmentioning
confidence: 99%
“…Peak identification was done by analyzing a chemically hydrolyzed sodium phytate sample. The order of the peaks has previously been described by Skoglund et al [22]. Since the detection response for the lower inositol phosphates is lower than for IP 6 (which was used to create the standard curve), theoretical correction factors were used [22].…”
Section: Identification Of Phytate Degradation Products Ip 5 -Ipmentioning
confidence: 99%